STEP as a Useful Tool to Screen for Diabetes-Specific Health-Related Problems in Community-Based Geriatric Patients- An Exploratory Secondary Analysis of Cross-Sectional Data - Carmienke, Solveig; Geier, Anne-Kathrin; Deutsch, Tobias; Rasche, Franz Maximilian; Frese, Thomas (Experimental and Clinical Endocrinology & Diabetes, 2020)
Background and Aims Comprehensive geriatric assessments are established tools for the identification of health problems in the elderly. So far, little is known about tailoring and targeting to facilitate their application. As a starting point for a tailored assessment of patients with diabetes, a highly prevalent health condition, we aimed to assess if the Standardized Assessment of Elderly People (STEP) is able to identify relevant differences in self-reported health problems between diabetic and non-diabetic patients.Patients and Methods We performed a secondary analysis of a cross-sectional study including 1007 adults (aged 65 and older) from 28 German general practices, evaluating the feasibility and usefulness of the self-administered STEP version. For this exploratory study we re-analysed the data and compared patients with and without diabetes.Results Out of 940 patients included in the secondary analysis, 248 (26.4%) had diabetes. Compared to non-diabetic patients, geriatric diabetic patients reported more often problems in activities of daily living, physical problems typically associated with diabetes such as urinary incontinence, visual impairment, mood disturbances, as well as the use of medical or social services. Most of our results were stable after adjusting for age, sex and body mass index.Conclusion We conclude that the self-administered version of the STEP tool may be used to screen for health problems typically associated with diabetes. Our results may guide the development of a tailored STEP-version specifically for diabetic patients. Further research might evaluate the adoption and usefulness of such a tool in every-day general practice.
Keywords: general practice; primary care; comprehensive geriatric assessment; STEP questionnaire; diabetes mellitus